Trajectory tracking control of autonomous marine vessel using neuro adaptive sliding mode control - Rossomando, Francisco Guido (2021)
This research paper presents the design of a control technique based on the combination of Linear Algebra (LABC) with Neuro Adaptive sliding mode control (NN-SMC) applied to the control of a marine vessel. Where the linear Algebra technique controls the kinematics of the Vessel and the Neuro Adaptive sliding mode control controls its dynamics. The simulation results show satisfactory results especially when there are disturbances acting on its dynamics. Finally the convergence of the proposed technique was demonstrated using Lyapunov's theory.